ABDOMEN ULTRASONOGRAPHIC EXAMINATION ANALYSIS IN THE CASE OF URINARY BLADDER DIVERTICULA AT CILEGON HOSPITAL: - - Wirya, Tirta; Sari, Gando; Bahri, Syamsul; Heru, Nursama; Utami, Resa Wantika (JAMBI MEDICAL JOURNAL "Jurnal Kedokteran dan Kesehatan", 2021)
ABSTRACT Diverticulum is outpouching of hollow (or fluid-filled) structures, which can form in various organs in the body. Increased intravesical pressure (3-5 times) causes the bladder mucosa to infiltrate itself between the bladder muscle bundles which results in the development of extravasational sacs or saccules which subsequently results in diverticulum formation. The sonographic diagnosis of bladder diverticula depends on the demonstration of communication between the bladder and the mass. When such communication, or estuary, is not seen during ultrasound examination, the bladder diverticulum can look like any other type of cystic pelvic mass. The approach used is descriptive qualitative. This study aims to analyze the examination of the USG Abdomen with clinical bladder diverticula to get an appropriate picture of USG so that the diagnosis can be established. The study population was patients who performed an abdominal USG examination at the Cilegon Regional General Hospital. The sample of this study were 1 (one) patient. The method used in collecting data in this study is observation, documentation, and literature study. Keywords: Ultrasound, Urinary Bladder, Diverticula